Penerapan sistem informasi akuntansi manajemen terhadap pengendalian kualitas produk pada Holland Bakery Manado - Wala, Tirsa Rosiana Lini; Nangoi, Grace B; Walandouw, Stanley Kho (Indonesia Accounting Journal, 2020)
Holland Bakery is a brand for modern bakery franchise networks with premium quality. Holland Bakery was first established in 1987 in Jakarta, under the auspiece of PT. Mustika Citra Rasa. Holland Bakery is the only Disney character licensee bakery in Indonesia. Holland Bakery has 22 branches that manage more than 400 outlets and will continue to be expanded nationally to other cities. The purpose of this research is to analyze the application of Management Accounting Information System to Product Quality Control in Holland Bakery Manado. This type of research is qualitative descriptive research. Based on the result of research that has been done, in the process of applying Management Accounting Information System to Product QualityÂ  Control in Holland Bakery Manado, researchers found their application of Total Quality Management in their business activities. With the exixtence of TQM in its business processes, the company can run smoothly and show positive results for the company.